PEMANFAATAN VIDEO PEMBELAJARAN MELALUI SMARTPHONE UNTUK MENINGKATKAN PENGUASAAN GRAMMAR PADA MATA PELAJARAN BAHASA INGGRIS DI SMAS MUHAMMADIYAH LEMPANGANG KABUPATEN GOWA - Dewi IndraSari, Citra; Daroe Iswatiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the use of instructional videos accessed through smartphones to improve students’ grammar mastery in English subjects at SMAS Muhammadiyah Lempangan. The research is motivated by students’ difficulties in understanding grammar concepts when taught through conventional methods, prompting the need for more engaging and flexible media. Using a qualitative descriptive approach, data were collected through classroom observations, in-depth interviews with teachers and students, and documentation of learning activities. The findings show that instructional videos provide clearer explanations of grammar rules through visual demonstrations, examples, and step-by-step presentations. Students reported that videos helped them better understand tenses, subject-verb agreement, and sentence patterns because they could replay the content as needed. The use of smartphones also increased learning motivation and enabled independent study both in class and at home. Furthermore, videos encouraged class participation, collaborative discussion, and improved digital literacy. Although several obstacles were found—such as internet limitations, distractions from other applications, and students’ device constraints—the overall impact of video-based learning was positive. The study concludes that instructional videos delivered via smartphones are effective, practical, and relevant to supporting grammar mastery in senior high school settings